Nawierzchnia z betonu wałowanego jako alternatywa dla dróg lokalnych = Roller compacted concrete as alternative for local roads - Radwański, Wojciech; Pytlowany, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The work presents principles of designing the concrete mixture composition and discusses technology of making the roller compacted concrete pavement. It presents a section of local road successfully realized in technology of roller compacted concrete on Wisze Street in Krosno.
Keywords: beton wałowany; drogi lokalne; niezawodność; roller compacted concrete (RCC); local road; reliability